Construction and Transformation of HVA1 Gene Expression Vector into Indonesian Elite Rice Varieties - Sri Koerniati; Hani Widhianata (Jurnal AgroBiogen, 2012)
of drought in rice. HVA1 is one of the Late EmbryogenesisAbundant (LEA) protein group that plays a role on cellprotection during stresses. A study was done with anobjective to construct a plasmid vector expressing HVA1 andto transform it into Indonesian elite rice varieties. Materialsused in the study were plasmid pBY520 (source of HVA1;intermediate plasmid pRP9; plasmid pAY560326(backbone); restriction enzymes BamHI, HindIII, XhoI, andSpeI; T4 DNA ligase, and gel DNA extraction kit. Methodsused were standard procedure for plasmid vectorconstruction and molecular biology. Step I: the pBY520 andpRP9 were cut with BamHI and HindIII, and electrophoratedwith 1% agarose gel. DNA fragments of HVA1 and pRP9 werepurified, ligated with T4 DNA ligase, and transformed intoEscherichia coli DH5-α by heat shock. E. coli were grownonto solid medium (+ kanamycin 100 mg/l). A new plasmidDNA was isolated from single colony culture of the bacteria,confirmed, and named pRP9_HVA1. Step II: DNA ofpRP9_HVA1 and pAY560326 were cut with XhoI dan SpeIenzymes, purified, and ligated. The next procedure wassimilar to step I, and the resulted plasmid was confirmed byPCR and digestion with XhoI dan SpeI enzymes, and namedpAY_HVA1. Step III: pAY_HVA1 was first transformed intoAgrobacterium EHA-105 and then into rive varieties Ciherangand Inpari 6 using the early infection of scutellumtransformation method. Nine transgenic rice lines thatpositively contain HVA1 were obtained.